Durability of a coating containing titanium dioxide for the photocatalytic degradation of diclofenac in water with UV‐A irradiation. (23rd July 2017) - Schulze‐Hennings, U.; Brückner, I.; Gebhardt, W.; Groteklaes, M.; Blöß, S. P.; Wett, M.; Linnemann, V.; Montag, D.; Pinnekamp, J.
Abstract: A novel catalyst was used for lab scale photocatalytic experiments. It was a carbon doped titanium dioxide which was designed to create an energy efficient photocatalytic process. The titanium dioxide is able to absorb UV‐A radiation and parts of the visible light spectrum. The catalyst was immobilized to a glass sheet. UV‐A radiation was used for the degradation of the pharmaceutical diclofenac in water to investigate the applicability of the catalyst to degrade organic micropollutants. With the given experimental setup hydroxyl radicals were generated and diclofenac was degraded below the limit of quantification. However, reaction rates are rather slow and the material properties of the catalyst showed the need of improvement. This is because the properties of the coating were influenced by the release of inorganic binder. Therefore, the coating and possibly the titanium dioxide were washed off and the reaction rates decreased drastically after 80 hours of use.